(NoSNOWI SISTEMNO)QÇ BÆOLOGÆÇ (B:s)E (NNAW^ALXNIJ POS)QÆBNIK (B/s)E - (NoKOL)QÆTENKO(B, (Nn(B. æ.,s)E; (NgRODZINSXKIJ(B, (Nd(B. (Nm(B.s ((NkI)QÇW (B:s)E (NlIB)QÆDX(B,s)E, 2005)
(Np)QÆDRU^NIK Z OSNOW SISTEMNOÇ BÆOLOGÆÇ(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (Nb)QÆOLOGÆQs)E; (NVITTQs; (NKL)QÆTINAs)E; (NW)QÆRUSIs)E; (NEKOSISTEMIs; (NEWOL@C)QÆQs)E; (NPROKAR)QÆOTIs)E; (NEUKAR)QÆOTIs)E